2020
DOI: 10.1021/jacs.9b12254
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Ferroelectricity of All-Inorganic Perovskite CsPbBr3 Quantum Dots

Abstract: The combination of ferroelectric–optical properties in halide perovskites has attracted tremendous interess because of its potential for optoelectronic and energy applications. However, very few reports focus on the ferroelectricity of all-inorganic halide perovskites quantum dots. Herein, we report a excellent ferroelectricity in CsPbBr3 quantum dots (QDs) with a saturation polarization of 0.25 μC/cm2. Differential scanning calorimetry, X-ray diffraction, and transmission electronic microscopy revealed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 40 publications
(24 reference statements)
4
53
0
Order By: Relevance
“…[ 18 ] Ferroelectric cesium lead tribromide (CsPbBr 3 ) NPs also show saturation polarization at room temperature, which is ascribed to the slightly mismatched centers of ferroelectric properties and positive charge due to orthorhombic CsPbBr 3 distortion units and off‐center cesium ions. [ 19 ] Here, CsPbBr 3 perovskite NPs were utilized to act as a polarizing layer, which was synthesized via a typical hot‐injection method according to a previously report. [ 20 ] To obtain stable and high‐photoluminescence (PL) CsPbBr 3 perovskite NPs, the thicknesses and lateral dimensions can be controlled by different ratios of short‐ and long‐chain ligands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 ] Ferroelectric cesium lead tribromide (CsPbBr 3 ) NPs also show saturation polarization at room temperature, which is ascribed to the slightly mismatched centers of ferroelectric properties and positive charge due to orthorhombic CsPbBr 3 distortion units and off‐center cesium ions. [ 19 ] Here, CsPbBr 3 perovskite NPs were utilized to act as a polarizing layer, which was synthesized via a typical hot‐injection method according to a previously report. [ 20 ] To obtain stable and high‐photoluminescence (PL) CsPbBr 3 perovskite NPs, the thicknesses and lateral dimensions can be controlled by different ratios of short‐ and long‐chain ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Figure a shows the UV–vis absorption and PL spectra of CsPbBr 3 NPs, which show the first exciton peak of 515 nm and PL peak of 520 nm, and they are lined well with the previous report. [ 19 ] The morphology and structure of CsPbBr 3 NPs were investigated by transmission electron microscopy (TEM). As shown in the inset of Figure 1b, the cubic‐shaped NPs exhibit an average size of ≈10 nm, and the size of the NPs is uniform, which means the diameter can be well controlled with suitable synthesis parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The ferroelectricity in halide perovskite quantum dots was also investigated. [ 123 ] It was demonstrated that a spontaneous polarization can emerge in CsPbBr 3 quantum dots due to phase change from cubic to orthorhombic structure. [ 123 ] In the orthorhombic phase, the [PbBr 6 ] [ 4 ]− octahedral distortion and the Cs + off‐centering are responsible for the spontaneous polarization, which lead to separated centers of positive and negative charges, resulting in ferroelectric polarization in CsPbBr 3 quantum dots.…”
Section: Low Dimensional Metal Halides Ferroelectricmentioning
confidence: 99%
“…[ 123 ] In the orthorhombic phase, the [PbBr 6 ] [ 4 ]− octahedral distortion and the Cs + off‐centering are responsible for the spontaneous polarization, which lead to separated centers of positive and negative charges, resulting in ferroelectric polarization in CsPbBr 3 quantum dots. [ 123 ]…”
Section: Low Dimensional Metal Halides Ferroelectricmentioning
confidence: 99%
See 1 more Smart Citation